Application of Block Notation Through Color Marking on the Piano of Grade Initial Students at Prodigy Music Academy - Ade Surya Akbar, Ade (Universitas Negeri Surabaya, 2025)
Prodigy Music Academy is a music course institution that provides guitar, bass guitar, piano, drums, vocal, and violin courses. The problem in this study is the difficulty of students distinguishing piano keys, so a color marking method is needed for initial-grade students. This study aims to analyze the color marking method and the results of student achievement in color marking at Prodigy Music Academy. The method applied in the research is descriptive qualitative through observation techniques, interviews, questionnaires, documentation, and descriptive data presentation. This research resulted in the application of the color method on the piano. The tools used were sticky notes and colored pens. The colors used are red, orange, yellow, green, blue, indigo, and purple. In terms of student achievement, the teacher provides summative and diagnostic evaluations. Questionnaires were distributed via Google form to 10 parents of students, with the results of parents giving positive assessments to students so that it was found that students were achieved in the color marking method.